Polycentricity, Islam, and Development : Potentials and Challenges in Pakistan. - Malik, Anas (Lexington Books, 2017)
Touching on development, polycentric governance, and Islamic and South Asian Studies, this book argues that religiously and historically-grounded shared understandings can support productive polycentric order in Pakistan and comparable Muslim-majority developing countries.